Identification and application of an endophytic fungus Arcopilus aureus from Panax notoginseng against crop fungal disease - Sun, Diangang; Li, Fengyang; Wang, Lingling; Chen, Ruige; Liu, Feng; Guo, Liwei; Li, Na; Zhang, Fuxian; Lei, Liancheng (Frontiers in Plant Science, 2024)
Endophytic fungi are important microbial resources for developing novel antibacterial and antifungal drugs to prevent and control crop diseases. Panax notoginseng has been used as a Chinese medicinal herb for a long time, as it has various bioactivities. However, information on endophytic fungi isolated from Panax notoginseng is rare. In this study, an endophytic fungus known as SQGX-6, which was later identified as the golden hair fungus Arcopilus aureus, was isolated from Panax notoginseng. SQGX-6 was extracted using ethyl acetate, and the active components of the fungus were identified using ultra-performance liquid chromatography-mass spectrometry (UHPLC-MS). The antifungal and antioxidant activities of the extract were determined and evaluated in vitro and in vivo. SQGX-6 and its extract inhibited the growth of Corn stalk rot (Fusarium graminearum), Corn southern leaf blight (Helminthosporium maydis), and Tomato gray mold (Botrytis cinerea) in vitro. The free radical scavenging rates for 2,2-Diphenyl-1-pyridinyl hydrazide (DPPH) radical scavenging activity, 3-Ethylbenzothiazoline-6-Sulfonic Acid Radical scavenging (ABTS) activity were also downregulated by the SQGX-6 extract. In vivo, the SQGX-6 extract inhibited the mycelial growth rates of the three aforementioned fungi and downregulated malondialdehyde (MDA) content and upregulated peroxidase (POD) and phenylalanine ammonia-lyase (PAL) content in fruits, leading to significant reduction in damage to cherry tomatoes caused by Botrytis cinerea. UHPLC-MS was performed to identify various active substances, including Alkaloids, Azoles, Benzofurans, Coumarins, Flavonoids, Organic acids, Phenols, and plant growth regulators contained in the extract. These results suggested that the endophytic fungus SQGX-6 of Panax notoginseng and its extract have excellent antifungal and antioxidant activities, and thus, it is an important microbial resource for the developing novel drugs against plant fungal infections.